জীবনের শিলালিপি - আহমেদ, কাজী শাহেদ, ১৯৪০- (ঢাকা : আগামী প্রকাশনী, 2014)
Autobiographical reminiscences of Kājī Śāheda Āhameda, born in 1940, Bengali author and publisher from Bangladesh.
Donated By Akbar Ali Khan
In Bengali.
Keywords: Ahmed, Kazi Shahid, -- 1940-; Authors, Bengali -- 19th century -- Biography; Publishers and publishing -- Bangladesh -- Biography